Field-induced charge-density-wave transitions in the organic metal α-(BEDT-TTF)2KHg(SCN)4 under pressure: Органические проводники - Andres, D.; Kartsovnik, M.V.; Biberacher, W.; Neumaier, K.; Sheikin, I.; Müller, H.; Kushch, N.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Successive magnetic-field-induced charge-density-wave transitions in the layered molecular conductorα-(BEDT-TTF)2KHg(SCN)4 are studied in the hydrostatic pressure regime, in which the zero field chargedensity-wave (CDW) state is completely suppressed. The orbital effect of the magnetic field is demonstrated torestore the density wave, while the orbital quantization induces transitions between different CDW states atchanging the field strength. The latter appear as distinct anomalies in the magnetoresistance as a function offield. The interplay between the orbital and Pauli paramagnetic effects acting, respectively, to enhance and to suppress the CDW instability is particularly manifest in the angular dependence of the field-induced anomalies.